A Pilot Study Examining Diagnostic Differences Among Exercise and Weight Suppression in Bulimia Nervosa and Binge Eating Disorder. (6th March 2015) - Cook, Brian J.; Steffen, Kristine J.; Mitchell, James E.; Otto, Maxwell; Crosby, Ross D.; Cao, Li; Wonderlich, Stephen A.; Crow, Scott; Hill, Laura; Le Grange, Daniel; Powers, Pauline
Abstract Objective The objective of this study was to investigate diagnostic differences in weight suppression (e.g., the difference between one's current body weight and highest non‐pregnancy adult body weight) and exercise among Bulimia Nervosa (BN) and Binge Eating Disorder (BED). Because exercise may be a key contributor to weight suppression in BN, we were interested in examining the potential moderating effect of exercise on weight suppression in BN or BED. Method Participants with BN (n = 774) and BED (n = 285) completed self‐report surveys of weight history, exercise and eating disorder symptoms. Generalised linear model analyses were used to examine the associations among diagnosis, exercise frequency and their interaction on weight suppression. Results Exercise frequency and BN/BED diagnosis were both associated with weight suppression. Additionally, exercise frequency moderated the relationship between diagnosis and weight suppression. Specifically, weight suppression was higher in BN than in BED among those with low exercise frequency but comparable in BN and BED among those with high exercise frequency. Discussion Our results suggest that exercise frequency may contribute to different weight suppression outcomes among BN and BED. This may inform clinical implications of exercise in these disorders. Specifically, much understanding of the differences among exercise frequency and the compensatory use of exercise in BN and BED is needed. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.